Islamization of knowledge and its intersection with the intellectual project of Malik Bin Nabi - Belkacem BENCHAIB (Social Sciences Journal, 2020)
The Islamization of knowledge is manifested in Malik bin Nabi's intellectual and cultural project inspired by the Islamic religion, which is characterized by objective knowledge based on the compatibility of the mind with the transfer according to the data of civilization and culture. The Islamization of knowledge is the application of religion to reality in terms of contemporary human thought Modern and corresponds to nature and existence